Measurement of the intersystem crossing yield of S4U within tRNA by time-resolved absorption bleching - Shaqiri, Z.; Angelov, D., fizičar; Vidolova-Angelova, E. (2008)
Summary: The rare base 4-thiouridine (s4U), present in various transfer RNA (tRNA) molecules from Escherichia coli, occupies usually the strategically important 8th position between the double helices of the acceptor and the dihydrouridine stems of the cloverleaf. This unusual base is largely used as an intrinsic build-in probe for RNA conformational and RNA(DNA)-protein interaction studies through triplet excited state photochemistry related to covalent adducts formation. Here, by applying laser transient absorption saturation spectroscopy, we measured the intersystem crossing yield jST and the excited triplet state absorption eT-T of s4U within tRNA. While the incorporation of s4U in tRNA induced appreciable changes in the latter, no important variation of the intersystem crossing yield was observed, which is in contrasts with the published data
Simboli u naslovu
Bibliografija: 12 jed
Sažetak
Keywords: Atomska i molekularna fizika -- Interakcije; Biofizika -- Interakcije molekula; Spektroskopija nuklearne magnetske rezonancije -- Primjena